A hypoallergenic peptide mix containing T cell epitopes of the clinically relevant house dust mite allergens. Issue 12 (3rd October 2019) - Huang, Huey‐Jy; Curin, Mirela; Banerjee, Srinita; Chen, Kuan‐Wei; Garmatiuk, Tetiana; Resch‐Marat, Yvonne; Carvalho‐Queiroz, Claudia; Blatt, Katharina; Gafvelin, Guro; Grönlund, Hans; Valent, Peter; Campana, Raffaela; et al.
Abstract: Background: In the house dust mite (HDM) Dermatophagoides pteronyssinus, Der p 1, 2, 5, 7, 21, and 23 have been identified as the most important allergens. The aim of this study was to define hypoallergenic peptides derived from the sequences of the six allergens and to use the peptides and the complete allergens to study antibody, T cell, and cytokine responses in sensitized and nonsensitized subjects. Methods: IgE reactivity of HDM‐allergic and non‐HDM‐sensitized individuals to 15 HDM allergens was established using ImmunoCAP ISAC technology. Thirty‐three peptides covering the sequences of the six HDM allergens were synthesized. Allergens and peptides were tested for IgE and IgG reactivity by ELISA and ImmunoCAP, respectively. Allergenic activity was determined by basophil activation. CD4+ T cell and cytokine responses were determined in PBMC cultures by CFSE dilution and Luminex technology, respectively. Results: House dust mite allergics showed IgE reactivity only to complete allergens, whereas 31 of the 33 peptides lacked relevant IgE reactivity and allergenic activity. IgG antibodies of HDM‐allergic and nonsensitized subjects were directed against peptide epitopes and higher allergen‐specific IgG levels were found in HDM allergics. PBMC from HDM‐allergics produced higher levels of IL‐5 whereas non‐HDM‐sensitized individuals mounted higher levels of IFN‐gamma, IL‐17, pro‐inflammatory cytokines, and IL‐10. Conclusion: IgG antibodies in HDM‐allergic patients recognize peptide epitopes which are different from the epitopes recognized by IgE. This may explain why naturally occurring allergen‐specific IgG antibodies do not protect against IgE‐mediated allergic inflammation. A mix of hypoallergenic peptides containing T cell epitopes of the most important HDM allergens was identified. Abstract : A mix of thirty‐one hypoallergenic peptides containing T cell epitopes of the six most important house dust mite (HDM) allergens was identified. Natural IgG antibodies of HDM‐allergic patients recognize different epitopes than IgE antibodies. Hypoallergenic T cell epitope‐containing peptides comprising the important HDM allergens may be used for therapy and prevention of HDM allergy.